Literature Study of the Sustainability Model of Transportation Facilities and Infrastructure in the Management of Public Transportation with the Concept of Inter-Regional Cooperation (Case in the City and District of Bogor) - Syaiful, Syaiful; Pratikso, Pratikso; Wiwoho Mudjanarko, Sri (ASTONJADRO, 2023)
Traffic in the city of Bogor is relatively high. With this level of density, the city of Bogor is classified as the second most congested city after DKI Jakarta. Achieving the process of transporting passengers and goods as optimally as possible in a certain space and time taking into account several factors such as safety, comfort, smoothness, time efficiency and costs according to these needs. The balance and needs of transportation facilities and infrastructure in achieving its goals is the real movement of each user. The main objective of this study is to formulate a model for the sustainability of transportation facilities and infrastructure in the management of public transport with the concept of inter-regional cooperation. The originality/novelty in the research is a) the handling of the model of sustainability of transportation facilities and public transport transportation infrastructure in the two regions of Bogor regency and Bogor city, b) the sustainability of the public transport management model with the concept of inter-regional cooperation, namely Bogor regency and Bogor city in reducing congestion between the two buffer city. The methods used are survey methods, interviews and studies of expert opinions. This concept is called MODEL SUSTAIN-SARPRASKOKABO_2023. By referring to this initial concept, it is hoped that a balanced and sustainable traffic pattern in Indonesia will soon be realized.